2014
DOI: 10.4103/2229-5178.131079
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of terbinafine hydrochloride 1% cream vs eberconazole nitrate 1% cream in localised tinea corporis and tinea cruris

Abstract: Aims:To study and compare the efficacy and safety of topical terbinafine hydrochloride 1% cream and eberconazole nitrate 1% cream in localized tinea corporis and cruris.Methods and Materials:Patients were randomized after considering various inclusion and exclusion criteria into two groups. Group A (treated with terbinafine 1% cream for 3 weeks) and group B (treated with eberconazole 1% cream for 3 weeks). The sample size was of 30 patients with 15 patients in each group. Assessment of clinical improvement, KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…8 Eberconazole is clinically effective in the treatment of topical fungal infections, with good safety profile and tolerability. 9,10 In our study, all three topical drugs were well tolerated and found to be safe. Local side effects such as erythema, swelling, stinging sensation, or itching as mentioned in a few studies were not reported.…”
Section: Discussionmentioning
confidence: 50%
“…8 Eberconazole is clinically effective in the treatment of topical fungal infections, with good safety profile and tolerability. 9,10 In our study, all three topical drugs were well tolerated and found to be safe. Local side effects such as erythema, swelling, stinging sensation, or itching as mentioned in a few studies were not reported.…”
Section: Discussionmentioning
confidence: 50%
“…In another study done by Choudhary et al ,[ 7 ] patients with tinea corporis and tinea cruris were treated with topical 1% terbinafine hydrochloride and 1% eberconazole nitrate cream respectively, twice daily for 3 weeks. There was 100% cure rate in both groups at the end of 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study comparing the efficacy and safety of eberconazole versus terbinafine had already been done on patients with tinea corporis and tinea cruris. [ 7 ] The present study was undertaken to compare the efficacy and safety of eberconazole versus terbinafine in TV.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a randomized control trial found similar efficacy and tolerability of 1% terbinafine cream to 1% eberconazole nitrate cream in the management of localized tinea corporis and cruris. [ 24 ] Similarly, another RCT found an efficacy of 1% terbinafine cream similar to 2% sertaconazole cream. [ 33 ] Various newer formulations, i.e., TBF-loaded liposome film, TBF-loaded liposome and ethosome, TBF-loaded transferosome, liposome poloxamer gel, microemulsion-based gel, and ethosome chitosan gel are in the developmental phase to increased penetration leading to augmented efficacy.…”
Section: Other Newer 14α-lanosterol Demethylase Inhibitorsmentioning
confidence: 97%
“…[ 23 ] A randomized controlled trial found the efficacy and safety of 1% eberconazole nitrate cream similar to that of 1% terbinafine hydrochloride cream in the treatment of localized (<20% involvement) tinea corporis and tinea cruris. [ 24 ] Recently, a study used ethyl cellulose microsponges as topical carriers of eberconazole nitrate and found four-fold higher retention of eberconazole nitrate in the stratum corneum layer compared with commercial cream,[ 25 ] which might lead to increased efficacy of the drug.…”
Section: Role Of Topical Antifungalsmentioning
confidence: 99%